2013
DOI: 10.1530/rep-13-0032
|View full text |Cite
|
Sign up to set email alerts
|

Changes in granulosa cells' gene expression associated with increased oocyte competence in bovine

Abstract: One of the challenges in mammalian reproduction is to understand the basic physiology of oocyte quality. It is believed that the follicle status is linked to developmental competence of the enclosed oocyte. To explore the link between follicles and competence in cows, previous research at our laboratory has developed an ovarian stimulation protocol that increases and then decreases oocyte quality according to the timing of oocyte recovery post-FSH withdrawal (coasting). Using this protocol, we have obtained th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 63 publications
3
70
0
2
Order By: Relevance
“…We compared the expression patterns of our differentially expressed genes with previously published data (36). In fact, Nivet et al (36) showed the gene expression patterns of granulosa cells that contained oocytes with better developmental potentials. Our data analysis indicates that FID induced expression of 81 genes, which is similar to Nivet et al in cumulus cells (Supplementary Table S1).…”
Section: Biofunction Analysis and Upstream Regulators Of Fidsensitivementioning
confidence: 91%
“…We compared the expression patterns of our differentially expressed genes with previously published data (36). In fact, Nivet et al (36) showed the gene expression patterns of granulosa cells that contained oocytes with better developmental potentials. Our data analysis indicates that FID induced expression of 81 genes, which is similar to Nivet et al in cumulus cells (Supplementary Table S1).…”
Section: Biofunction Analysis and Upstream Regulators Of Fidsensitivementioning
confidence: 91%
“…All datasets were generated using the EmbryoGENE bovine transcriptome microarray (24). Each experiment focused on a specific cell-type within the ovarian follicle: granulosa cells (21), cumulus cells (5), and the GVBD oocyte (18). Each cell type was analyzed at 20, 44, 68, and 92 h of FSH coasting after ovarian superstimulation with this hormone.…”
Section: Data Retrievalmentioning
confidence: 99%
“…We subsequently analyzed the effect of FSH coasting for 20, 44, 68, and 92 h on the transcriptomic profiles of granulosa cells (21), cumulus cells (5) and germinal-vesicle breakdown (GVBD) oocytes (18) using same technological platform. In the present study, we performed a meta-analysis of our previous studies in an attempt to identify one or more gene networks active in all three follicular compartments and correlated with FSH coasting time and acquisition of oocyte developmental competence.…”
mentioning
confidence: 99%
“…The literature provides a complex picture of the molecules associated with oocyte competence at different molecular level: proteomics, transcriptomics (Jiang et al, 2010;Gilbert et al, 2012;Nivet et al, 2013) and metabolomics (Matoba et al, 2014). Furthermore, numerous studies focused on the characterization of the expression profiles of granulosa cells from follicles at different developmental stages (Hatzirodos et al, 2014b;Girard et al, 2015) and physiological condition (Hatzirodos et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%